Both tumour cells and infiltrating T-cells in equine sarcoids express FOXP3 associated with an immune-supressed cytokine microenvironment. (December 2016) - Wilson, A.; Hicks, Chelsea
Abstract Bovine papillomavirus (BPV) infections of equine species have a central role in the aetiology of equine sarcoids; a common benign skin tumour of horses, zebras and donkeys. Within the lesions, all of the early papillomavirus genes are expressed and promote the excessive replication of fibroblasts which characterise these tumours. Equine sarcoids differ from BPV induced fibro-papillomas of cattle (the natural host of BPV), in that they do not produce high amounts of virus particles, do not usually regress spontaneously and do not sero-convert to BPV; features which suggest that affected horses lack an effective anti-viral immune response to BPV. Equine sarcoids contain large numbers of CD4+ CD8+ dual positive T-cells which uniformly express FOXP3, the key transcription factor of regulatory T-cells, and FOXP3 is also expressed within the BPV infected fibroblasts. Compared to healthy skin, sarcoids showed increased mRNA transcription for FOXP3 and the regulatory cytokine TGFβ. Transcription of IL17, which has been shown to have a regulatory function in human papillomavirus-associated tumours, was also elevated in equine sarcoids compared to spleen. In contrast, the levels of mRNA transcripts for effector T cell cytokines IL2, IL4 and interferon-gamma (IFNγ) were not elevated in sarcoids compared to healthy skin or spleen. Similarly neither interferon-alpha (IFNα), interferon-beta (IFNβ) nor IL12 family members were elevated in sarcoids compared to normal skin. We suggest that the regulatory cytokine micro-environment within sarcoids enables the persistence of the lesions by preventing an effective anti-viral immune response.